Pembangunan kemahiran kerja berpasukan menerusi kokurikulum sukan hoki dalam kalangan pelajar UTHM - Buhari, Alunawati (2015)
Involvement in co-curricular activities is important in addition to teaching and learning processes at all levels, including Higher Education Institutions to create soft skills among students. This study was conducted to identify the application, awareness and control of teamwork skills through curricular hockey at Universiti Tun Hussein Onn Malaysia (UTHM). The study design was chosen by the researchers is a case study because the information is obtained more precisely and to answer specific research questions. This study uses triangulation method to analyse the data of questionnaires, interviews, observations and document analysis. Numbers of samples involved in this study were 73 students who make up the total population. The results of the questionnaire were analysed using Statistical Package for Social Science (SPSS) Version 20 to obtain the mean and standard deviation. The findings indicate that there is infusion of teamwork skills in co-curricular hockey at UTHM. This study suggests that instructors or lecturers as a change agent in implementing effective teamwork skills which in turn can produce human capital that are competitive in the global market.